Avaliação dos serviços sócio assistenciais para o morador de rua: o caso Curitiba - Brandt, Silvia Helena (2012)
The following research has the objective of evaluating the Social Assistance Policy‟s social inclusion programs executed by the city of Curitiba to it‟s homeless population. This research utilized a fundamentally qualitative methodological approach. The Data was obtained together with primary and secondary sources. In relation to the primary sources, 9 semi-structured interviews took place with 9 random homeless persons in the city of Curitiba – Paraná, from both genders and ages between 18 and 65 years old. The secondary data was gathered though consulting public domain documentation (from the city‟s inclusive programs) and unsystematic observation on the search field. In relation to the data‟s synthesizing process, descriptive and qualitative procedures took place. The adopted theoretical reference was based on authors of the Community Social Psycology (Monteiro, 2003; Vidal, 2007; Sandoval, 2000) and of the historical sociology (Vigotski, 1193, 1994; Góis, 2008; Gonzáles Rey, 2002, 2003, 2004 and 2005 and Aguiar and Ozella, 2006). The study allowed us to conclude that, under the eyes of a homeless person, the programs are efficient on the matter of granting the rights of welfare recognized on the 1988‟s Federal Constitution. In other words: The safety and caressing of welcoming and 14 social relationships, as well as one‟s right to exercise citizenship (Sent to the confection of documents), even though not showing efficiency on social reintegration through work. Therefore, we can also conclude that the professionals that work with the homeless people, as well as politics destined to them have to look at each subject as an individual, developing strength and capability to conquer the rooting on the alienation from society, born from social stigmas themselves, and leaving the social assistance‟s client situation surviving, relating and caring for themselves.